ALI KHAMENEI DAN KETAHANAN IDEOLOGIS IRAN: KEPEMIMPINAN SPIRITUAL-MILITER DALAM MENGELOLA SUMBER DAYA UNTUK RESISTENSI NASIONAL - Ely Asyer Sitompul; Nur Rochmad Ibrohim, Tarsisius Susilo, Budi Saroso, Beny Leonard Limbong (JOURNAL OF LAW AND NATION, 2026)
Ayatollah Ali Khamenei, as Iran’s Supreme Leader, combines spiritual authority with military influence in his leadership. Under Khamenei, Iran faces severe international sanctions and global pressure, yet has endured through strong ideological resilience. This paper analyzes how integrating ideology (values of the Islamic Revolution and Shi’ism) with Iran’s self-reliant defense strategies (such as the resistance economy and domestic military development) has been key to national resistance. Khamenei launched the “Resistance Economy” concept emphasizing self-sufficiency and diversification for example, achieving fuel independence by building domestic refineries, bolstering food security, and developing defense technology (local drones and ballistic missiles) Khamenei’s spiritual-military leadership –legitimized by the principle of Wilayat al-Faqih enables him to guide the people ideologically while also controlling military strategy, as seen when he issued a fatwa banning nuclear weapons yet still pushed for strengthened civilian nuclear capacity. In comparison, Indonesia’s defense is guided by the Pancasila ideology and the 1945 patriotic values. This study compares Iran’s principle of ideological resilience with that of Indonesia, which, although different (theocracy vs. Pancasila), both emphasize ideological strength in defense. The findings indicate that a strong state ideology can foster national solidarity against threats, with the caveat that differing contexts require strategic adaptation. Implication: Indonesia can learn from Iran the importance of ideological resilience, but apply it according to Pancasila values making Indonesia’s defense resolute in protecting sovereignty while remaining humane.